Characteristics of Postmodernism Reflected on Designs of ready-to-wear Children’s Clothing Using their Artistic Drawings - Sabbagh, Wesam (Advances in Social Sciences Research Journal, 2024)
This study aims to simplify the postmodernism’s characteristics to create innovative fashion designs for children’s ready-to-wear clothing. By incorporating children’s artistic drawings, the study seeks to achieve the designs’ functional, aesthetic, and productive aspects. The significance of this research lies in enriching the practices of the ready-to-wear children’s clothing industry through the utilization of postmodernism characteristics. A descriptive analytical approach was employed to identify the relevant characteristics of the postmodernism and adapt them to the design process for children’s clothing. Eight designs were created and evaluated by specialists using a study tool. The results revealed statistically significant differences in the evaluations of the designs across various aspects. The aesthetic aspect received the highest evaluation, followed by the production and, finally, the functional aspects. The study concluded that the design incorporating the attribute of ambiguity was the most highly rated among the designs, considering all aspects. Based on these findings, the study recommends further exploration of the postmodernism in fashion design and an in-depth study of international arts to foster creativity and diversity in children’s clothing design.